2006
DOI: 10.1007/s10681-006-9247-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of salt tolerance in a recombinant inbred population of wheat (Triticum aestivum L.)

Abstract: A population of 114 recombinant inbred lines (RILs), derived from the cross Opata85 · W7984, was used to genetically analyze the response of wheat to salt stress. This analysis resulted in the identification of 47 QTL mapping to all wheat chromosomes except 1B, 1D, 4B, 5D and 7D. Of these QTL, 10 were effective during the germination stage, and 37 at the seedling stage. Many of the traits related to salt tolerance mapped to common chromosome intervals, such as Xglk683-Xcdo460 on chromosome 3A, Xfbb168-Xbcd147 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 39 publications
3
66
1
Order By: Relevance
“…Thus, proline content in plant tissues was used as a marker-assisted selection molecule in some breeding programs that endeavored to improve salinity and drought tolerance in plants (Flowers and Flowers, 2005;Ma et al, 2007;Ashraf and Foolad, 2013;Wu et al, 2013). In the present study, I determined whether proline accumulation in the date palm tree was specifically correlated to drought, and high salinity conditions, or was a general response to abiotic stresses.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, proline content in plant tissues was used as a marker-assisted selection molecule in some breeding programs that endeavored to improve salinity and drought tolerance in plants (Flowers and Flowers, 2005;Ma et al, 2007;Ashraf and Foolad, 2013;Wu et al, 2013). In the present study, I determined whether proline accumulation in the date palm tree was specifically correlated to drought, and high salinity conditions, or was a general response to abiotic stresses.…”
Section: Introductionmentioning
confidence: 97%
“…However, during the last decade microsatellites or SSR markers have been extensively used for genetic diversity study, genome mapping, varietal identification, etc. Utilization of these markers to investigate the genetic variations and QTL mapping for salt tolerance in different cultivars has been previously reported by some researchers (Liu et al, 2001;Munns, 2002;Ma et al, 2007;Kurup et al, 2009). The potential of these markers to investigate genetic diversity for salinity tolerance in Pakistani wheat landrace genotypes/cultivars is very limited.…”
Section: Introductionmentioning
confidence: 98%
“…Usually, QTL analysis in saline hydroponics reports several chromosomes associated with ST (eg. Ma et al 2007), while QTLs on chromosomes 5B and 5D were identified in a field experiment with saline irrigation (Quarrie et al 2005). The Kna1 gene was identified on chromosome 4D controlling Na + and K + accumulation in the shoot (Dubcovsky et al 1996).…”
mentioning
confidence: 99%